Characterization of Biochar Produced from IRAQI Palm Fronds by Thermal Pyrolysis - Alwan, Qasim H.; Rahman, Ameel Mohammed; Salman, Mohanned Hassib; Ali, Zainab Hassan (Al-Khwarizmi Engineering Journal, 2015)
AbstractThe present paper focuses in a particular on the study of the biochar production conditions by the thermal pyrolysis of biomass from local Iraqi palm fronds, in the absence of oxygen. The biochar product can be used as soil improvers. The effect of temperature on the extent of the thermal pyrolysis process was studied in the range from 523 to 773K with a residence time of 15 minutes and nitrogen gas flow rate of 0.1 l/min. The produced biochar was characterized as will as biomass and degradation products. The results showed that the rate of biochar production decreases with the increasing in temperature, also it was noted that the normalized biochar surface area and pore size increases with the increasing in temperature.The results showed an increase in the biochar ability to absorb water and the percent of water content increases with increasing temperature. The quality and quantity of the products of the thermal pyrolysis of biomass depend directly on the temperature and on the biomass basic composition of the compounds: hemicellulose, cellulose and lignin.FTIR analysis gave an excellent description to the nature of the active groups on the biochar surface. These groups vary with the temperature and biochar composition (i.e. hemicellulose, cellulose and  lignin).